Perspectives on Complex Understandings - Pedersen, Jan; Matamala, Anna (Journal of Audiovisual Translation, 2020)
This special issue contains a peer-reviewed selection of papers presented at Media for All 9: Complex understandings, a conference which took place in Stockholm in 2019. This introduction links the 15 articles included in this special issue to the conference theme, which is also the theme of this volume: complex understandings. The ultimate aim of the research presented here is to throw light on the various and complex perspectives, processes, views and agents involved in audiovisual translation and media accessibility. This introductory article highlight the main points of the different papers, and it also organises the contributions according to the different perspectives they take: product-based studies, process-based studies, training-based studies, user-based studies and policy-based studies. Overall, this volume offers a thorough overview of state-of-the-art research in audiovisual translation and media accessibility.